Recommendations for Increasing Physician Provision of Pre-Exposure Prophylaxis: Implications for Medical Student Training - Robert L. Cooper PhD, MSSW; Paul D. Juarez PhD; Matthew C. Morris PhD; Aramandla Ramesh PhD; Ryan Edgerton MPH; Lauren L. Brown PhD, LCSW, MSSW; Leandro Mena MD; Samuel A. MacMaster PhD; Shavonne Collins MD; Patricia Matthews- Juarez PhD; Mohammad Tabatabai PhD; Katherine Y. Brown EdD; et al. (SAGE Publishing, 2021)
There is growing evidence that pre-exposure prophylaxis (PrEP) prevents HIV acquisition. However, in the United States, approximately only 4% of people who could benefit from PrEP are currently receiving it, and it is estimated only 1 in 5 physicians has ever prescribed PrEP. We conducted a scoping review to gain an understanding of physician-identified barriers to PrEP provision. Four overarching barriers presented in the literature: Purview Paradox, Patient Financial Constraints, Risk Compensation, and Concern for ART Resistance. Considering the physician-identified barriers, we make recommendations for how physicians and students may work to increase PrEP knowledge and competence along each stage of the PrEP cascade. We recommend adopting HIV risk assessment as a standard of care, improving physician ability to identify PrEP candidates, improving physician interest and ability in encouraging PrEP uptake, and increasing utilization of continuous care management to ensure retention and adherence to PrEP.